Lip Cream Preparation Formulation From Red Dragon Fruit (Hylocereus Polyrhizus L.) As A Natural Coloring - Halifa Nasir, Nurul; Syafriah, Wa Ode; Yolandari, Sri (International Journal of Multidisciplinary Learners, 2025)
Lip cream is the most commonly used type of lip makeup among women. A natural dye called anthocyanins is found in the red dragon fruit (Hylocereus polyrhizus).. Red dragon fruit has a striking red color that can be used as a safe and attractive natural coloring material for use in cosmetic products. This study aims to formulate red dragon fruit as a natural dye in lip cream preparations and test the evaluation of the preparation. This study is an experimental study that formulates red dragon fruit using 3 concentrations of red dragon fruit F1 (15%), F2 (20%) and F3 (25%) as natural dyes. The evaluation test methods for lip cream preparations are organoleptic test, homogeneity test, application power test and pH test. The results of the evaluation of the lip-cream organoleptic test with the concentration of red dragon fruit dye F1 (15%) were cream while the concentration of red dragon fruit F2 (20%) was light pink and the concentration of red dragon fruit F3 (25%) was dark pink. The homogeneity test of F1, F2 and F3 has an even color, no coarse grains. The applicability test on F1, F2 and F3 had a difference in color produced in the application of lip cream due to the difference in the concentration of red dragon fruit extract used. Finally, the pH test obtained FI (4.54), F2 (4.33) and F3 (4.03). The results of the evaluation test of preparations from F1, F2 and F3 that have a good formula are F3.